2018
DOI: 10.1148/radiol.2018171995
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Osteochondritis Dissecans: Cartilage T2 Mapping of Stable Medial Femoral Condyle Lesions

Abstract: Purpose To determine whether a T2 mapping sequence could depict early changes in the composition and microstructure of cartilage overlying stable lesions of the medial femoral condyle in patients with juvenile osteochondritis dissecans (JOCD). Materials and Methods This retrospective study analyzed a sagittal T2 mapping sequence performed between September 1, 2015, and March 31, 2017, on 16 patients (10 boys and six girls; median age, 11.5 years) with 18 stable medial femoral condyle JOCD lesions and 18 age-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
4
15
0
1
Order By: Relevance
“…Studies have shown that the T2 value of the nucleus pulposus and fibrous rings of the intervertebral disc is significantly related to the water content and weakly related to the proteoglycan content 16 . The alignment and content of collagen fibers and water content in CEP are the main determinants of the T2 value 20,40 . T2 mapping imaging technology can reflect the tissue macromolecular environment and changes in biochemical components, including water, proteoglycans, and collagen by measuring the T2 relaxation time 36 .…”
Section: Role Of Cartilage Endplates In the Degeneration Of Intervertmentioning
confidence: 99%
“…Studies have shown that the T2 value of the nucleus pulposus and fibrous rings of the intervertebral disc is significantly related to the water content and weakly related to the proteoglycan content 16 . The alignment and content of collagen fibers and water content in CEP are the main determinants of the T2 value 20,40 . T2 mapping imaging technology can reflect the tissue macromolecular environment and changes in biochemical components, including water, proteoglycans, and collagen by measuring the T2 relaxation time 36 .…”
Section: Role Of Cartilage Endplates In the Degeneration Of Intervertmentioning
confidence: 99%
“…T 2 mapping has been introduced into clinical practice for various organs and tissues, including brain, heart, and cartilage . In neuroradiology, a microstructural change, such as neuronal loss or demyelination, results in increased free water and thus longer T 2 relaxation times and greater signal intensity on T 2 ‐weighted MRI images .…”
mentioning
confidence: 99%
“…T 2 mapping has been introduced into clinical practice for various organs and tissues, including brain, [6][7][8] heart, 4,9 and cartilage. 5,[10][11][12] In neuroradiology, a microstructural change, such as neuronal loss or demyelination, results in increased free water and thus longer T 2 relaxation times and greater signal intensity on T 2 -weighted MRI images. 13 Furthermore, T 2 mapping is used to assess cartilage damage in musculoskeletal imaging [10][11][12] and to evaluate cardiac edema and fibrosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T2 mapping is able to detect changes in the chondral collagen matrix and in the overall water content of the cartilage 9 . T2 mapping has been established and validated for detection and quantification of these early degenerative changes in various joints, including the knee, metacarpophalangeal joints, wrist, and ankle 7,[14][15][16] . Higher T2 values indicate damage to the three-dimensional collagen network and an increase in the water content [15][16][17] .…”
mentioning
confidence: 99%